The archaeal and bacterial community structure in composted cow manures is defined by the original populations: a shotgun metagenomic approach - Romero-Yahuitl, Vanessa; Zarco-González, Karla Estephanía; Toriz-Nava, Ana Lilia; Hernández, Mauricio; Velázquez-Fernández, Jesús Bernardino; Navarro-Noya, Yendi E.; Luna-Guido, Marco; Dendooven, Luc (Frontiers in Microbiology, 2024)
Organic wastes are composted to increase their plant nutritional value, but little is known how this might alter the bacterial and archaeal community structure, and their genes. Cow manure was collected from three local small-scale farmers, composted under controlled conditions while the bacterial and archaeal communities were determined using shotgun metagenomics at the onset and after 74 days of composting. The bacterial, archaeal, methanogen, methanotrophs, methylotroph and nitrifying community structure and their genes were affected by composting for 74 days, but the changes were determined by the original composition of these communities. Most of these archaeal and bacterial groups showed large variation after composting, but also between the cow manures. The differences in the relative abundance of their genes, however, was much smaller compared to that of the archaeal or bacterial groups. It was found that composting of different cow manures did not result in similar bacterial or archaeal communities and the changes that were found after 74 days were defined by the original populations, although more research is necessary to determine if other composting conditions will give the same results.